The horse in the gourd = Het paard in de kalebas - Dumas, Charlotte 1977- (Japanmuseum SieboldHuis, 2018)
The film and photos tell the story of 12-year-old Yuzu and her horse Urara. Together with 5 main objects they form the leitmotif of this exhibition. The horse in Dumas' photographs is of a rare breed that is threatened with extinction. Through Yuzu's eyes we see the horse, her surroundings and the elements that at times plague then pamper nature. The circle of life in all its fragility and salvation, water and wind are the elements that exemplify this presentation while enchantment and mastery are at the heart. In addition to the five main objects, Dumas has selected Japanese prints, historic photos and drawings from private and public collections and combined them with work of her own for this exhibition. Exhibition: SieboldHuis, Leiden, The Netherlands (08.06.-25.11.2018)